2017
DOI: 10.1074/jbc.m117.781047
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characterization of β cell-adaptive and -maladaptive mechanisms during chronic high-fat feeding in C57BL/6NTac mice

Abstract: The onset of type 2 diabetes is characterized by transition from successful to failed insulin secretory compensation to obesity-related insulin resistance and dysmetabolism. Energy-rich diets in rodents are commonly studied models of compensatory increases in both insulin secretion and β cell mass. However, the mechanisms of these adaptive responses are incompletely understood, and it is also unclear why these responses eventually fail. We measured the temporal trends of glucose homeostasis, insulin secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 56 publications
16
68
0
Order By: Relevance
“…As expected [20], islet hypertrophy developed due to this chronic hyperinsulinemia, as found in HFD-fed male mice, and normalized in offspring of NAC-treated mice which had improved insulin sensitivity. The expansion of β-cell might be attributed not only to islet hypertrophy, but also to neogenesis of islets, leading to an increase in their number, as found in HFD-fed male mice and as also reported previously [21]. Such an increase in islet number was not detected either in HFD-fed female mice or in male offspring of NAC-treated mice, which had a better sensitivity to insulin.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As expected [20], islet hypertrophy developed due to this chronic hyperinsulinemia, as found in HFD-fed male mice, and normalized in offspring of NAC-treated mice which had improved insulin sensitivity. The expansion of β-cell might be attributed not only to islet hypertrophy, but also to neogenesis of islets, leading to an increase in their number, as found in HFD-fed male mice and as also reported previously [21]. Such an increase in islet number was not detected either in HFD-fed female mice or in male offspring of NAC-treated mice, which had a better sensitivity to insulin.…”
Section: Discussionsupporting
confidence: 68%
“…Sci. 2020, 21,1981 14 of 21 been anesthetized by ketamine+xylazine as required, and all efforts were made to minimize suffering. Animal House operates in compliance with the rules and guidelines of the Israel Council for Research in Animals, based on the US NIH Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…A major piece of evidence for this new role of obese ATM EVs in regulating β cell functions comes from the reconstitution of obese ATMs-secreted EVs in vivo by intravenous injection into the recipients starting HFD feeding. In line with previous findings(14,47), in contrast to the prolonged obesity-induced expansions of proinflammatory M1 macrophages and beta cell populations, 4 weeks HFD feeding led to modest growth rates of β cell mass and proinflammatory M1 ATM population. After elevating the level of obese ATM EVs by multiple intravenous injections, HFD recipient mice had less glucose-stimulated insulin secretion and insulin levels at feeding condition, while the supplementation of obese ATM EVs led to more proliferating ki67+ β cells.…”
supporting
confidence: 92%
“…In humans, similar compensatory increases in augmented insulin secretion have been reported in obese, nondiabetic patients and individuals with prediabetes (36,37). In addition to elevated insulin secretion, a study of HFD-fed C57BL/6NTac (B6N) mice demonstrated hyperexpression of genes known to promote β cell function and differentiation, including many key β cell transcriptional factors (11). The same study identified the transient upregulation of UPR genes to protect against decompensating ER stress responses.…”
Section: β Cell Responses In Metsmentioning
confidence: 63%
“…Metabolic syndrome presents a set of unique stressors to the β cell, including elevated glucose, increased free fatty acids, and inflammation (11)(12)(13). In this adverse environment, β cells initially mount a compensatory response to ramp up β cell functional capacity and insulin secretion to meet the elevated metabolic demand.…”
Section: β Cell Responses In Metsmentioning
confidence: 99%